Probing of sub-picometer vertical differential resolutions using cavity plasmons - Wen Chen (Nature Portfolio, 2018)
Plasmon rulers can be used for resolving ultrasmall material changes. Here, the authors show how cavity plasmons in a metal nanowire-on-mirror setup can be used to probe vertical dimensional changes with sub-picometer differential resolution using two carefully chosen material systems.